Kain Hitam Cave (Painted Cave) Niah, Sarawak: The Relationship of Boat-Shaped Coffin and Rock Painting - Junior Kimwah; Humin Jusilin; Zaimie Sahibil (AMER ABRA cE-Baby e-International Publishing House, Ltd, 2020)
This paper discusses the relevance that exists in a cave used as a place of residence since the time of Neolithic. This archaeological site contains important artefact that show modern civilization (homo sapiens) at the end of the Neolithic period. This research focuses on the cultural development of the ancient people through the discovery of artefact in the Kain Hitam Cave. Preliminary findings show that ritual activities have been practised. Initial conclusions indicate that the ancient people practised animism. The linkages between the two aspects are essential in giving new insight into the cultural elements they were practising years ago.